Asymptotics in statistics : some basic concepts - Le Cam, Lucien M. (Lucien Marie), 1924-; Yang, Grace Lo. (New York : Springer, 2000)
"This volume is the second edition of a work that presents a coherent introduction to the subject of asymptotic statistics as it has developed in the past fifty years. The second edition differs from the first in that it has been made more "reader friendly." It also includes a new chapter, Chapter 4, on Gaussian and Poisson experiments because of their growing role in the field, especially in nonparametrics and semiparametrics.
Most of the subsequent chapters have been entirely rewritten, and the nonparametrics of Chapter 7 have been amplified.".
"Much of the material has been taught in a second-year graduate course at Berkeley for thirty years. It represents a link between traditional material, including maximum likelihood and Wald's theory of statistical decision functions, together with comparison and distances for experiments. This volume is not intended to replace monographs on specialized subjects, but it will help to place them in a coherent perspective."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Mathematical statistics -- Asymptotic theory